2012
DOI: 10.3797/scipharm.1106-13
|View full text |Cite
|
Sign up to set email alerts
|

Relaxant Effect of Essential Oil of Artemisia herba-alba Asso. on Rodent Jejunum Contractions

Abstract: Artemisia herba-alba Asso. is a shrub commonly encountered in Morocco. It is used in traditional medicine for treating intestinal disorders. The essential oil extracted from the plant’s aerial parts reversibly relaxed the spontaneous tonus of the rabbit jejunum in a reversible concentration dependent manner with an IC50 value of 97.33 ± 2.59 ng/ml and reversed the tonic contraction of rat jejunum induced by 75 mM KCl and 10−6 M carbachol with IC50 values of 115.5 ± 3.05 and 119.4 ± 20.86 ng/ml, respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…(LABSAP-9) Chih (Ap) Inf, Dec٫ Mac Gastric disorders, liver problems, wormer, muscle spasm, hypertension, COVID-19 0.76 (Eddouks et al 2002;Boudjelal et al 2013;Ouelbani et al 2016;Kharchoufa et al 2018) (Boudjelal et al 2013;Miara et al 2013Miara et al , 2019aBenarba et al 2015;Benarba 2016) infertility, menstrual cycle problems, cough, toothache 0.33 (Miara et al 2013;Benarba 2016;Ouelbani et al 2016;Hamza et al 2019) may be due to its chemical compounds as monoterpenoids, sesquiterpenoids (largely in essential oils), flavonoids, and phenolic compounds (Khlifi et al 2013;Mohamed et al 2019) Several studies studied the antispasmodic activity of the essential oil extracted from the plant's aerial parts. It was found that the administration of this oil relaxed the spontaneous tonus of the rabbit jejunum and reversed the tonic contraction of rat jejunum induced by carbachol (Aziz et al 2012). Another published study has found that the aqueous extract of this plant has increased the time of gastrointestinal transit in alloxan-treated rabbits and mice (Marrif et al 1995), and improves insulin sensitivity and hepatic steatosis in rodents-induced metabolic syndrome (Réggami et al 2019).…”
Section: )mentioning
confidence: 95%
“…(LABSAP-9) Chih (Ap) Inf, Dec٫ Mac Gastric disorders, liver problems, wormer, muscle spasm, hypertension, COVID-19 0.76 (Eddouks et al 2002;Boudjelal et al 2013;Ouelbani et al 2016;Kharchoufa et al 2018) (Boudjelal et al 2013;Miara et al 2013Miara et al , 2019aBenarba et al 2015;Benarba 2016) infertility, menstrual cycle problems, cough, toothache 0.33 (Miara et al 2013;Benarba 2016;Ouelbani et al 2016;Hamza et al 2019) may be due to its chemical compounds as monoterpenoids, sesquiterpenoids (largely in essential oils), flavonoids, and phenolic compounds (Khlifi et al 2013;Mohamed et al 2019) Several studies studied the antispasmodic activity of the essential oil extracted from the plant's aerial parts. It was found that the administration of this oil relaxed the spontaneous tonus of the rabbit jejunum and reversed the tonic contraction of rat jejunum induced by carbachol (Aziz et al 2012). Another published study has found that the aqueous extract of this plant has increased the time of gastrointestinal transit in alloxan-treated rabbits and mice (Marrif et al 1995), and improves insulin sensitivity and hepatic steatosis in rodents-induced metabolic syndrome (Réggami et al 2019).…”
Section: )mentioning
confidence: 95%
“…Relaxant effect of its essential oil on rodent jejunum contractions (Aziz et al 2012). Aniticoccidiosis effect in broilers (Messai et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Many studies have demonstrated the effect of free radical scavenging, antimicrobial activities, anticarcinogenicity 13,14 and dilation of blood vessel. [15][16][17][18] Recently, it has been also shown that the extract from Artemisia species had the vasorelaxing activity on thoracic aorta in rat through the endothelial NOS (eNOS)/cGMP pathway. 19,20 The penis is a vascular organ and has similar physical characteristics in vascular smooth muscle.…”
Section: Introductionmentioning
confidence: 99%